THE IMPORTANCE OF MORTGAGE LOANS AND SUBSIDIES IN DIGITAL ECONOMY - Abdivaitova Umida Azamat qizi; Zarina Ravshanovna Rahimova (Journals Park Publishing, 2023)
This article presents considerations for the study and implementation of the Decree of the President of the Republic of Uzbekistan “On measures to implement the program for providing housing to the population through mortgage loans based on market principles in 2023” (April 13, 2023). Citizens with the use of digital technologies are shown ways to implement the program of providing housing to the population through mortgage loans.
Keywords: mortgage, loan, subsidy, mortgage loans, economy, digital economy.